An Improved Two-Step Protocol for Trophoblast Differentiation of Human Pluripotent Stem Cells - Horii, Mariko (Curr Protoc Stem Cell Biol, 2019)
We previously established a two-step protocol for differentiation of human pluripotent stem cells (hPSC) into trophoblast, using a StemPro-based minimal media (EMIM) with Bone Morphogenetic Protein-4 (BMP4). However, this protocol was suboptimal, resulting in induction of mixed mesoderm and trophoblast markers. Furthermore, adapting hPSCs to StemPro has proven difficult, and prolonged culture in this media has been shown to promote genomic instability. Therefore, we moved on to use of new media, including E8, and most recently, StemFlex, for rapid adaptation from feeder to non-feeder conditions. In the new protocol, we have incorporated the WNT inhibitor IWP2 into the first step, resulting in uniform differentiation of hPSCs into cytotrophoblast-like cells, without induction of the mesoderm lineage. We also show that, at the end of the second step, there are distinct populations of terminally-differentiated multinucleated hCG-producing syncytiotrophoblast- and HLAG(+) extravillous trophoblast-like cells.